Changes in muscle stiffness of the trapezius muscle after application of ischemic compression into myofascial trigger points in professional basketball players - Kisilewicz, A.; Janusiak, M.; Szafraniec, R.; Smoter, M.; Ciszek, B.; Madeleine, P.; Fernández-de-Las-Penas, C.; Kawczynski, A. (Journal of Human Kinetics, 2018)
The study aimed to assess the effects of compression trigger point therapy on the stiffness of the trapezius muscle in professional basketball players (Part A), and the reliability of the MyotonPRO device in clinical evaluation of athletes (Part B). Twelve professional basketball players participated in Part A of the study (mean age: 19.8 ± 2.4 years, body height 197 ± 8.2 cm, body mass: 91.8 ± 11.8 kg), with unilateral neck or shoulder pain at the dominant side. Part B tested twelve right-handed male athletes (mean ± SD; age: 20.4 ± 1.2 years; body height: 178.6 ± 7.7 cm; body mass: 73.2 ± 12.6 kg). Stiffness measurements were obtained directly before and after a single session trigger point compression therapy. Measurements were performed bilaterally over 5 points covering the trapezius muscle. The effects were evaluated using a full-factorial repeated measure ANOVA and the Bonferroni post-hoc test for equal variance. A p-value < .05 was considered significant. The RM ANOVA revealed a significant decrease in muscle stiffness for the upper trapezius muscle. Specifically, muscle stiffness decreased from 243.7 ± 30.5 to 215.0 ± 48.5 N/m (11.8%), (p = .008) (Part A). The test-retest relative reliability of trapezius muscle stiffness was found to be high (ICC from 0.821 to 0.913 for measurement points). The average SEM was 23.59 N/m and the MDC 65.34 N/m, respectively (Part B). The present study showed that a single session of compression trigger point therapy can be used to significantly decrease the stiffness of the upper trapezius among professional basketball players. Keywords: myofascial pain syndrome; soft tissue therapy; sports medicine; myotonometry